The philosophy of martial arts - the example of the concept of Ido - Wojciech J. Cynarski (Karolinum Press, 2017)
The Ido philosophy is a proposal to clarify the meaning of today's warrior pathway. The author tries to answer the following questions: In what way should we understand epistemology? How do we describe the human being and the phenomenon of martial arts? What is the meaning of the terms 'idō' and 'Idōkan'? What ethics, values and rules are prominent in the Ido? What is the specific, symbolic content of the Ido? This is a single case study, involving a content analysis of literature and the wider discourse, and the hermeneutic phenomenology. Epistemology is understood here as a way of understanding the martial arts by the practitioner, and as a way of reaching the truth about the philosophy of martial arts. In both cases it is the practice that is their own psychophysical experience. Man and the phenomenon of martial arts (ontology) here we treat holistically. 'Ido' is an ambiguous concept, but in Ido philosophy we understand it in the first place as the principle of 'continuous movement'. The prevailing ethic is derivative of the tradition of chivalry, which is also accented in symbolism. The Ido philosophy, as an anthropology of martial arts and today's Warrior Way, draws from the wisdom of the East and the West, but not uncritically. Normative ethics realizes the ideals of nobility, as Homo Creator Nobilis. This indicates the way in which value requires great effort, self-discipline and perseverance. It focuses especially on timeless, higher values, such as fidelity, truth, and the pursuit of wisdom.